Polarizing glass and method for producing same

By rationally designing the glass components and ultraviolet exposure treatment, uniform silver core is formed, and the problem of phase-dividing emulsion in the existing glass polarizer during the smelting process is solved, and high extinction ratio and excellent polarization performance are achieved.

CN119707283APending Publication Date: 2025-03-28CDGM GLASS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411788496.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing glass polarizers are prone to phase separation emulsion during the smelting process, resulting in poor extinction ratio and low polarization performance when the Ag+ content is insufficient.

Method used

By rationally designing cationic and anionic components, including Si4+, B3+, R+, Ag+, etc., the Ag+/Ce4+ ratio and B3+/Ag+ ratio are controlled, and combined with ultraviolet exposure treatment, a uniform silver core is formed to promote the generation and stretching of silver halide clusters.

Benefits of technology

Polarized glass with high extinction ratio is achieved, which improves polarization performance, reduces insertion loss, and avoids the problem of phase separation of glass during smelting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707283A_ABST
    Figure CN119707283A_ABST
Patent Text Reader

Abstract

Provided is a polarizing glass having a high extinction ratio. The polarizing glass comprises the following components in molar percentage: cationic components: 28-55% of Si < 4 + >, 15-35% of B < 3 + >, 1-35% of R < + > and 0.01-0.2% of Ag < + >, and R < + > is one or more of Li < + >, Na < + > and K < + >; and the anion component contains 99 to 99.9 percent of O2 <-> and 0.1 to 1 percent of Cl <-> and Br <->. Through reasonable component design, the polarizing glass has a high extinction ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to polarized glass, in particular to linear polarized glass and a manufacturing method thereof. Background Art

[0002] Polarizers are important optical devices. According to polarization characteristics, they can be divided into linear polarizers, elliptical polarizers, circular polarizers, etc., among which linear polarizers are more commonly used. Currently, the linear polarizers available on the market include organic polarizers and glass polarizers. Compared with traditional organic polarizers, glass polarizers have high strength, good weather resistance and stability, and are widely used in polarization-related optical isolators, optical modulators, laser printers and other equipment; in addition, the miniaturization of polarization glass meets the needs of miniaturization and integration of optical devices, and can be widely used in the fields of optical storage and fiber optic sensing.

[0003] Polarized glass selectively absorbs natural light and only transmits polarized light in a specific direction. Its polarization performance mainly comes from the wire-grid-shaped metal particles inside the glass. Photons vibrating parallel to the length direction of the metal particles are absorbed by the electron plasma oscillation of the metal particles and converted into heat energy, while photons vibrating perpendicular to the length direction of the metal particles pass through unimpeded, thereby realizing the conversion of non-polarized light into linear polarized light. In the prior art, glass polarizers mainly use single-element Ag or single-element Cu as polarizing materials. In the borosilicate glass system, polarized glass with single-element Ag as polarizing particles is prepared. As Ag in the glass + As the content of Ag increases, the glass is very likely to undergo phase separation and opacity during the melting process, which has an adverse effect on the final extinction ratio of the glass. + When the content is insufficient, sufficient linear metal polarizing material cannot be formed, resulting in relatively low extinction of the polarized glass. Summary of the invention

[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide a polarizing glass with a higher extinction ratio.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] Polarized glass, its components are expressed in molar percentage, the cationic component contains: Si 4+ :28~55%、B 3+ :15~35%、R + :1~35%、Ag + :0.01~0.2%,the R + For Li + 、Na + , K + One or more of;

[0007] The anion component contains: O 2- :99~99.9%、Cl - +Br - :0.1~1%.

[0008] Furthermore, the polarized glass, whose components are expressed in molar percentage, the cationic component also contains: Al 3+ :0~12%, and / or Zr 4+ :0~5%, and / or Zn 2+ :0~3.5%, and / or Ti 4+ :0~2%, and / or Cu 2+ :0~0.1%、and / or Ce 4+ :0~0.1%.

[0009] Polarized glass, its components are expressed in molar percentage, the cation component is Si 4+ :28~55%、B 3+ :15~35%、R + :1~35%、Ag + :0.01~0.2%、Al 3+ :0~12%、Zr 4+ :0~5%、Zn 2+ :0~3.5%、Ti 4+ :0~2%、Cu 2+ :0~0.1%、Ce 4+ :0~0.1%composition, the R + For Li + 、Na + , K + One or more of;

[0010] The anion component is O 2- :99~99.9% and Cl - +Br - : 0.1~1% composition.

[0011] Furthermore, the components of the polarizing glass are expressed in molar percentage, wherein: Ag + / Ce 4+ 0.5~4.5, preferably Ag + / Ce 4+ 1.0~3.0; and / or B 3+ / Ag + 150~2500, preferably B 3+ / Ag + It ranges from 200 to 1500.

[0012] Furthermore, the components of the polarized glass are expressed in molar percentage, wherein: Si4+ :30~45%、and / or B 3+ :20~30%、and / or R + : 11-30%, preferably R + :20~30%, and / or Ag + :0.03~0.1%, and / or Al 3+ :3~10%, and / or Zr 4+ :0.5~3%, and / or Zn 2+ :0.5~2.5%, and / or Ti 4+ :0.5~1.5%, and / or Cu 2+ :0~0.05%, and / or Ce 4+ :0~0.06%.

[0013] Furthermore, the components of the polarizing glass are expressed in molar percentage, wherein: Li + : 0-12%, preferably Li + :0~9%、and / or Na + : 0-25%, preferably Na + :5~15%、and / or K + : 0~10%, preferably K + :2~8%.

[0014] Furthermore, the components of the polarizing glass are expressed in molar percentage, wherein: 2- :99.4~99.9%, and / or Cl - +Br - :0.1~0.6%.

[0015] Furthermore, the components of the polarizing glass are expressed in molar percentage, wherein: Cl - :0.1~0.8%, preferably Cl - :0.1~0.5%, and / or Br - : 0~0.3%, preferably Br - :0~0.2%.

[0016] Furthermore, the transmittance of polarizing glass with a thickness of less than 0.8 mm is more than 80%, preferably more than 85%, more preferably more than 90%; and / or the extinction ratio at 1550 nm is more than 20 dB, preferably more than 30 dB, more preferably more than 40 dB; and / or the extinction ratio at 1310 nm is more than 30 dB, preferably more than 40 dB, more preferably more than 50 dB; and / or the insertion loss at 1550 nm is less than 0.50 dB, preferably less than 0.40 dB, more preferably less than 0.30 dB; and / or the insertion loss at 1310 nm is less than 0.70 dB, preferably less than 0.60 dB, more preferably less than 0.40 dB.

[0017] Matrix glass, its composition is expressed in mole percentage, the cation component contains: Si 4+ :28~55%、B 3+ :15~35%、R + :1~35%、Ag + :0.01~0.2%,the R + For Li + 、Na + , K + One or more of;

[0018] The anion component contains: O 2- :99~99.9%、Cl - +Br - :0.1~1%.

[0019] Furthermore, the matrix glass, whose components are expressed in molar percentage, also contains the following cation components: Al 3+ :0~12%, and / or Zr 4+ :0~5%, and / or Zn 2+ :0~3.5%, and / or Ti 4+ :0~2%, and / or Cu 2+ :0~0.1%、and / or Ce 4+ :0~0.1%.

[0020] Furthermore, the matrix glass, its components are expressed in molar percentage, wherein: Ag + / Ce 4+ 0.5~4.5, preferably Ag + / Ce 4+ 1.0~3.0; and / or B 3+ / Ag + 150~2500, preferably B 3+ / Ag + It ranges from 200 to 1500.

[0021] Furthermore, the components of the matrix glass are expressed in molar percentage, wherein: Si 4+ :30~45%、and / or B 3+ :20~30%、and / or R + : 11-30%, preferably R + :20~30%, and / or Ag + :0.03~0.1%, and / or Al 3+ :3~10%, and / or Zr 4+ :0.5~3%, and / or Zn 2+ :0.5~2.5%, and / or Ti 4+ :0.5~1.5%, and / or Cu 2+ :0~0.05%, and / or Ce 4+ :0~0.06%.

[0022] Furthermore, the components of the matrix glass are expressed in molar percentage, wherein: Li + : 0-12%, preferably Li + :0~9%、and / or Na + : 0-25%, preferably Na + :5~15%、and / or K + : 0~10%, preferably K + :2~8%.

[0023] Furthermore, the components of the matrix glass are expressed in molar percentage, wherein: 2- :99.4~99.9%, and / or Cl - +Br - :0.1~0.6%.

[0024] Furthermore, the components of the matrix glass are expressed in molar percentage, wherein: Cl - :0.1~0.8%, preferably Cl - :0.1~0.5%, and / or Br - : 0~0.3%, preferably Br - :0~0.2%.

[0025] The polarizing element is made of the above-mentioned polarizing glass.

[0026] A device comprising the polarizing glass or the polarizing element mentioned above.

[0027] A method for manufacturing polarizing glass, the method comprising the following steps: 1) forming a matrix glass; 2) heat treatment; 3) stretching treatment; 4) reduction treatment.

[0028] Furthermore, in the method for manufacturing the polarized glass, ultraviolet exposure treatment is performed before heat treatment of the matrix glass.

[0029] Furthermore, in the method for manufacturing polarized glass, the ultraviolet exposure treatment is: cutting the matrix glass into long strips and polishing the large surface, and then exposing the matrix glass to ultraviolet light, preferably the exposure wavelength is 308-320nm, and the ultraviolet exposure time is preferably greater than 0 but less than or equal to 30 minutes, more preferably 10-25 minutes, and further preferably 15-25 minutes.

[0030] Furthermore, in the method for manufacturing polarized glass, the melting temperature of the matrix glass is 1200-1400°C, the melting time is 5-20 hours, the clarification temperature is 1300-1500°C, the clarification time is 6-8 hours, the annealing temperature is 500-600°C, the annealing time is 6-10 hours, and an oxidizing gas is introduced into the melting furnace during the smelting process.

[0031] Furthermore, in the method for manufacturing polarized glass, the heat treatment is: heating the matrix glass at a temperature ≥ T g + (100-200°C) for 10-20 hours. g is the transition temperature of the matrix glass.

[0032] Furthermore, in the method for manufacturing the polarized glass, the stretching process is: f ~(T f The glass is stretched at a temperature of 50°C to stretch the spherical silver halide clusters inside the glass into long strips or elliptical clusters with an aspect ratio of ≥2:1. f is the softening temperature of the matrix glass.

[0033] Furthermore, in the method for manufacturing polarized glass, the reduction treatment is: reducing the glass in a reducing atmosphere so that the long strips or elliptical silver halide clusters on the surface of the glass are reduced to elemental silver, and the reduction temperature is preferably greater than 200°C but less than the melting point of the silver halide.

[0034] The beneficial effect of the present invention is that through reasonable component design, the polarized glass of the present invention has a higher extinction ratio.

[0035] In some embodiments, Ag in the glass can be removed by UV exposure during the manufacturing process of the glass of the present invention. + Under the premise that the content is not high, the matrix glass is exposed to ultraviolet light to form uniform silver nuclei inside the matrix glass, which is conducive to the generation of sufficient silver halide clusters in the subsequent heat treatment process and improves the utilization rate of silver ions in the matrix glass, thereby producing a linear polarized glass with better extinction ratio performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the SEM image of Example 3 of the present invention.

[0037] Figure 2 This is the SEM image of Example 14 of the present invention. DETAILED DESCRIPTION

[0038] The following is a detailed description of the embodiment of the polarized glass of the present invention, but the present invention is not limited to the following embodiment, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of the description of the repeated description, the main purpose of the invention will not be limited by this. In the following content, the polarized glass of the present invention is sometimes referred to as glass.

[0039] [Polarized glass]

[0040] The following is an explanation of the scope of each component (ingredient) of the polarized glass of the present invention. In this specification, unless otherwise specified, the content of the cationic component is expressed as the molar percentage (mol%) of the cation in all cationic components, and the content of the anionic component is expressed as the molar percentage of the anion in all anionic components; the ratio between the contents of the cationic components is the ratio of the molar percentage contents of the contents of the various cationic components; the ratio between the contents of the anionic components is the ratio of the molar percentage contents of the contents of the various anionic components; and the total content is expressed in terms of ionic molar percentage. It should be noted that the ionic valence of each component in the present invention is a representative value used for convenience and is no different from other ionic valences. Some elements involved in the following description may have one or more possible valence states (including simple substances), and are described in this specification using a representative valence state of the element.

[0041] In the description of the relationship between the contents of the components in the present invention, when it involves a multiplication and / or division relationship, the component contents are calculated using the actual values ​​corresponding to their percentages. For example, when the component content percentage is 10%, it is calculated as 0.1 in the multiplication and / or division relationship.

[0042] Unless otherwise indicated in specific circumstances, the numerical ranges listed herein include upper and lower limits, "above" and "below" include endpoint values, and all integers or fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0043] <Cationic component>

[0044] Si 4+ A uniform network structure is formed inside the glass, thus forming the glass skeleton.4+ When the content of Si is below 28%, the mechanical strength, thermal stability, chemical stability and other properties of the glass will be reduced; 4+ When the content of Si exceeds 55%, the melting temperature of the glass increases, the viscosity increases, the melting becomes difficult, and the glass is prone to defects such as bubbles and stones. 4+ The content of is 28-55%, preferably 30-45%. In some embodiments, it may include 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41.5%, 42.5%, 43.5%, 44.5%, 45.5%, 46.5%, 47.5%, 48.5%, 49.5%, 50.5%, 51.5%, 52.5%, 53.5%, 54.5%, 55.5%, 56.5%, 57.5%, 58.5%, 59.5%, 51.5%, 52.5%, 5 %, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, 55% Si 4+ .

[0045] B 3+ It is one of the main components of glass. 4 ]、[BO 3 ] exist in two forms, and a proper amount can play a role in fluxing. 3+ With [BO 4 ] in the form of B, it can form a uniform network structure with silicon-oxygen tetrahedron, improving the chemical stability, thermal stability, thermal expansion coefficient and other properties of the glass. 3+ The content increased, [BO 4 ]To[BO 3 ] transformation, the glass has a phase separation trend. Under a certain temperature and time, [BO 3 ] gradually aggregate to form a boron-rich phase, which is conducive to promoting the formation and growth of silver halide clusters. 3+ The lower limit of the content is 15%, and the preferred lower limit is 20%. 3+ , [BO 3 ] content further increases, the network structure of the glass is destroyed, resulting in intensified phase separation, and the chemical stability, thermal stability, transmittance and extinction ratio of the glass deteriorate. 3+The upper limit of the content is 35%, and the preferred upper limit is 30%. In some embodiments, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35% B 3+ .

[0046] Al 3+ Can be used with Si 4+ Together they form a network structure, improving the mechanical strength and chemical stability of the glass while inhibiting the strong phase separation of the glass. 3+ When the content is too high, the viscosity of the glass increases, the melting temperature is high, and it is easy to produce defects such as stones. At the same time, it is not conducive to the precipitation of silver halide particles during the heat treatment of the matrix glass. 3+ The content of Al is 0-12%, preferably 3-10%. In some embodiments, 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% Al may be included. 3+ .

[0047] Zr 4+ It can inhibit the phase separation during the glass forming process and improve the weather resistance of the glass. However, if its content is too high, it will make the glass difficult to melt, cause the glass to form stones, and inhibit the phase separation during the heat treatment of the matrix glass. 4+ The content of Zr is 0-5%, preferably 0.5-3%. In some embodiments, Zr may include 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. 4+ .

[0048] Alkali Metal R + (R + For Li + 、Na + , K + One or more of them) as network external body components can play a role in fluxing, which is beneficial to lower the melting temperature and clarification temperature of the glass, but R+ Too high a content of R will destroy the glass network skeleton, resulting in poor performance of glass such as strength, chemical stability, and thermal stability. + The content of is 1-35%, preferably 11-30%, and more preferably 20-30%. In some embodiments, it may include 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 80%, 8.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35% of R + .

[0049] The glass contains two or more alkali metal components, and the mixed alkali effect formed helps to improve the weather resistance of the glass. + The content of Na is 0 to 12%, preferably 0 to 9%; + The content of K is 0 to 25%, preferably 5 to 15%; + The content of Li is 0-10%, preferably 2-8%. In some embodiments, 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% Li can be included. +In some embodiments, the present invention may include 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 1 2%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5 %, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25% Na + In some embodiments, the K content may include 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. + .

[0050] Zn 2+ It can lower the melting temperature of glass and improve its weather resistance. 2+ It can make the glass material longer, which is beneficial to the process adjustment of glass stretching. 2+ It will reduce the transmittance of the glass and make the extinction ratio of the glass worse. 2+ The content of Zn is 0-3.5%, preferably 0.5-2.5%. In some embodiments, 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5% Zn may be included. 2+ .

[0051] Ti 4+ It can improve the weather resistance and refractive index of glass. 4+ It has the ability to absorb ultraviolet light, and a proper amount of it can help inhibit the photochromism of glass; but if Ti 4+ Too high a content can easily cause glass devitrification. 4+The content of Ti is 0-2%, preferably 0.5-1.5%. In some embodiments, 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% Ti may be included. 4+ .

[0052] Ag + It is one of the important components of the present invention. As a polarizing substance in glass, it can improve the extinction ratio of glass. + When the content is too low, the density and particle size of the polarizing particles finally formed are too small to make the glass surface show polarization characteristics. + Too high a content will cause opacity and devitrification during the glass melting and forming process, and will also cause excessive growth of silver halide clusters during the heat treatment process, resulting in a decrease in the distribution density, which in turn will lead to a decrease in the extinction ratio of the glass and a decrease in the polarization performance of the glass. + The content of Ag is 0.01% to 0.2%, preferably 0.03% to 0.1%. In some embodiments, Ag may be contained in an amount of 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% + .

[0053] In some embodiments, control B 3+ The content of Ag + The ratio of the content of 3+ / Ag + In the range of 150 to 2500, it is beneficial to suppress the phase separation tendency of the glass melting process and improve the polarization performance of the glass. 3+ / Ag + 150 to 2500, more preferably B 3+ / Ag + In some embodiments, B 3+ / Ag +150, 160, 170, 180, 190, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1150, 1200, 1250, 1300, 1350, 1400, 1450, 1500, 1550, 1600, 1650, 1700, 1750, 1800, 1850, 1900, 1950, 2000, 2050, 2100, 2150, 2200, 2250, 2300, 2350, 2400, 2450, 2500.

[0054] Cu 2+ Can prevent Ag + It is reduced during the smelting process and the glass does not contain Cu. 2+ When Cu 2+ Too much Cu will cause serious coloring of the glass and affect the transmittance and polarization properties of the glass. 2+ The content of Cu is 0-0.1%, preferably 0-0.05%. In some embodiments, it may contain 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% Cu 2+ .

[0055] Ce 4+ As a photosensitizer, it separates electrons during UV exposure, making Ag + Reduced to Ag 0 But Ce 4+ Too high a content can easily cause glass coloring and affect the transmittance of the glass. 4+ The content of Ce is 0-0.1%, preferably 0-0.06%. In some embodiments, Ce may contain 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% 4+ .

[0056] In some embodiments, controlling Ag + The content of Ce 4+ The ratio of Ag content + / Ce 4+ In the range of 0.5 to 4.5, it is beneficial to control the amount of silver nuclei generated during exposure and avoid Ag + Ag is over-reduced, which affects the subsequent precipitation of silver halide clusters and improves the transmittance and extinction ratio of the glass. + / Ce4+ 0.5 to 4.5, more preferably Ag + / Ce 4+ In some embodiments, Ag + / Ce 4+ The values ​​are 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5.

[0057] <Anion component>

[0058] O 2- It is the main anion component of the glass of the present invention. In order to obtain the excellent performance of the present invention, O 2- The content of O is 99-99.9%, preferably 99.4-99.9%. In some embodiments, it may contain 99%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9% O 2- .

[0059] During the heat treatment, the halogen components form silver halide clusters with silver ions, with a melting point of 430-455°C, which is conducive to the subsequent stretching to form long strips of silver halide clusters. - Br - The mixed migration ion effect of the two halogen components can slow down the diffusion rate of the halogen and inhibit the re-spheroidization of the stretched silver halide when heated. However, excessive halogen components will cause opacity in the glass melting and annealing process, resulting in a decrease in glass transmittance and polarization performance. Therefore, the Cl - +Br - In some embodiments, Cl - +Br - It can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%.

[0060] In some embodiments, Cl - The content of Br is preferably 0.1 to 0.8%, more preferably 0.1 to 0.5%; -The content of Cl is preferably 0-0.3%, more preferably 0-0.2%. In some embodiments, it may contain 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8% Cl - In some embodiments, 0.1%, 0.15%, 0.2%, 0.25%, 0.3% Br may be included. - .

[0061] The "does not contain" and "0%" recorded in this article mean that the compound, molecule, ion or element is not intentionally added as a raw material to the glass of the present invention; however, as raw materials and / or equipment for producing glass, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final glass. This situation is also within the scope of protection of the patent of this invention.

[0062] Next, the performance of the polarizing glass of the present invention will be described.

[0063] [Light transmittance]

[0064] The light transmittance described in the present invention is external transmittance, sometimes referred to as transmittance.

[0065] The polarizing glass of the present invention was measured for average light transmittance at 1260 to 1650 nm using a Hitachi U-41000 spectrophotometer.

[0066] In some embodiments, the transmittance of the polarizing glass with a thickness of 0.8 mm or less is 80% or more, preferably 85% or more, and more preferably 90% or more.

[0067] In some embodiments, the thickness of the polarized glass sample is 0.1 mm, 0.2 mm, 0.3 mm, 0.5 mm, 0.7 mm, or 0.8 mm.

[0068] [Extinction ratio]

[0069] The extinction ratio of the polarized glass was tested using an extinction ratio tester to obtain the extinction ratios of the glass at 1310nm and 1550nm.

[0070] The extinction ratio tester uses a polarizer to generate linearly polarized light in a specific direction. The sample is placed in the analyzer. As the analyzer rotates, the maximum transmittance T of the sample is obtained. max and minimum transmittance T min The calculation formula of extinction ratio is:

[0071]

[0072] In some embodiments, the extinction ratio of the polarizing glass with a thickness of 0.8 mm or less at 1550 nm is greater than 20 dB, preferably greater than 30 dB, and more preferably greater than 40 dB.

[0073] In some embodiments, the extinction ratio of the polarizing glass with a thickness of 0.8 mm or less at 1310 nm is greater than 30 dB, preferably greater than 40 dB, and more preferably greater than 50 dB.

[0074] In some embodiments, the thickness of the polarized glass sample is 0.1 mm, 0.2 mm, 0.3 mm, 0.5 mm, 0.7 mm, or 0.8 mm.

[0075] [Insertion loss]

[0076] The insertion loss of the polarized glass was tested using an extinction ratio tester to obtain the insertion loss of the glass at 1310nm and 1550nm.

[0077] The incident light quantity T before inserting into the sample is measured by the extinction ratio tester. in , and the maximum transmittance T after inserting the sample max The calculation formula for insertion loss is:

[0078]

[0079] In some embodiments, the insertion loss of polarizing glass with a thickness of 0.8 mm or less at 1550 nm is 0.50 dB or less, preferably 0.40 dB or less, and more preferably 0.30 dB or less.

[0080] In some embodiments, the insertion loss of polarizing glass with a thickness of 0.8 mm or less at 1310 nm is 0.70 dB or less, preferably 0.60 dB or less, and more preferably 0.40 dB or less.

[0081] In some embodiments, the thickness of the polarized glass sample is 0.1 mm, 0.2 mm, 0.3 mm, 0.5 mm, 0.7 mm, or 0.8 mm.

[0082] The polarizing glass of the present invention can be used to make polarizing elements due to the above-mentioned excellent properties, and can be applied to polarization-dependent optical isolators, optical fiber polarizers, spectrophotometers and other equipment.

[0083] [Method for producing polarizing glass]

[0084] The present invention provides a method for preparing polarized glass, the method comprising the following steps:

[0085] 1) Forming matrix glass: Weigh and mix the glass raw materials according to the proportion of glass components, stir them evenly and add them to a melting furnace (such as platinum or platinum alloy crucible), melt them at 1200-1400℃ for 5-20 hours, then heat them to 1300-1500℃ for clarification for 6-8 hours, cool them down and homogenize them, pour them into a mold to form them, anneal them at 500-600℃ for 6-10 hours and then cool them naturally to obtain matrix glass. During the melting process, oxidizing gas is introduced into the melting furnace to maintain an oxidizing atmosphere in the furnace to prevent Ag + The present invention includes but is not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, chlorides, bromides, simple substances, etc. as glass raw materials.

[0086] In some embodiments, the matrix glass can be sampled and subjected to differential thermal analysis to obtain the transition temperature (T g ).

[0087] 2) Heat treatment: Heat the matrix glass at a temperature ≥ T g The heat treatment is preferably carried out at 100 to 200°C for 10 to 20 hours.

[0088] 3) Stretching treatment: at T f ~(T f The heat-treated glass is stretched within a temperature range of 100 °C to 50 °C, so that the spherical silver halide clusters inside the glass are stretched into long strips or elliptical clusters with an aspect ratio of ≥ 2:1. f In some embodiments, the glass surface after the stretching process may be polished.

[0089] 4) Reduction treatment: The stretched glass is reduced in a reducing atmosphere to reduce the long strips or elliptical silver halide clusters on the surface of the glass to elemental silver. The preferred reduction temperature is greater than 200°C, but the maximum reduction temperature is less than the melting point of the silver halide.

[0090] The polarized glass of the present invention is obtained by the above method. In the process of manufacturing the polarized glass from the matrix glass of the present invention, no other components are added, so the components and contents of the matrix glass are the same as those of the polarized glass.

[0091] The present invention also provides a second method for preparing polarized glass, the method comprising the following steps:

[0092] 1) Forming matrix glass: Weigh and mix the glass raw materials according to the proportion of glass components, stir them evenly and add them to a melting furnace (such as platinum or platinum alloy crucible), melt them at 1200-1400℃ for 5-20 hours, then heat them to 1300-1500℃ for clarification for 6-8 hours, cool them down and homogenize them, pour them into a mold to form them, anneal them at 500-600℃ for 6-10 hours and then cool them naturally to obtain matrix glass. During the melting process, oxidizing gas is introduced into the melting furnace to maintain an oxidizing atmosphere in the furnace to prevent Ag + The present invention includes but is not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, chlorides, bromides, simple substances, etc. as glass raw materials.

[0093] In some embodiments, the matrix glass can be sampled and subjected to differential thermal analysis to obtain the transition temperature (T g ).

[0094] 2) UV exposure treatment: Cut the matrix glass into long strips and perform large surface polishing, then perform UV exposure on the matrix glass. The UV exposure wavelength is preferably 308-320nm. Too long exposure time will cause Ag in the matrix glass to + Fully reduced to Ag 0 , affecting the subsequent silver halide cluster generation and stretching. Therefore, the ultraviolet exposure time is preferably greater than 0 but less than or equal to 30 minutes, more preferably 10 to 25 minutes, and further preferably 15 to 25 minutes.

[0095] Too high a silver content in the matrix glass can easily promote a violent phase separation of the glass during the melting and forming process, causing serious declines in the final transmittance, insertion loss and transmittance of the polarized glass. The inventors have found through extensive research that in the manufacturing process of polarized glass, a silver nucleus with a certain depth and uniform distribution can be formed on the glass surface by ultraviolet exposure treatment, which promotes the full utilization of silver ions inside the matrix glass during the heat treatment process, and precipitates silver halide clusters at a lower temperature and faster, effectively improving the extinction ratio of the polarized glass and reducing the insertion loss. At the same time, the ultraviolet exposure treatment can reduce the amount of silver introduced into the glass component, avoiding violent phase separation during the melting and forming process of the matrix glass.

[0096] 3) Heat treatment: Heat the matrix glass at a temperature ≥ T g The heat treatment is carried out in the range of + (100-200°C), and the heat treatment time is preferably 10-20 hours, so that the inside of the matrix glass, especially the silver core, aggregates to form spherical silver halide clusters with a diameter of 50-200nm.

[0097] 4) Stretching treatment: at T f ~(T fThe heat-treated glass is stretched within a temperature range of 100 °C to 50 °C, so that the spherical silver halide clusters inside the glass are stretched into long strips or elliptical clusters with an aspect ratio of ≥ 2:1. f In some embodiments, the glass surface after the stretching process may be polished for a second time.

[0098] 5) Reduction treatment: The stretched glass is reduced in a reducing atmosphere so that the long strips or elliptical silver halide clusters on the surface of the glass are reduced to elemental silver. The preferred reduction temperature is greater than 200°C, but the maximum reduction temperature is less than the melting point of the silver halide.

[0099] The polarized glass of the present invention is obtained by the above method. In the process of manufacturing the polarized glass from the matrix glass of the present invention, no other components are added, so the components and contents of the matrix glass are the same as those of the polarized glass.

[0100] Example

[0101] In some embodiments, the present invention adopts the above-mentioned method 2 for manufacturing polarized glass to obtain polarized glass shown in Tables 1 and 2. In addition, the performance of each polarized glass is measured by the test method described in the present invention, and the measurement results are shown in Tables 1 and 2. The thickness of the performance test sample in this embodiment is 0.5 mm.

[0102] Table 1.

[0103]

[0104]

[0105] Table 2.

[0106]

[0107]

[0108] In some embodiments, the present invention adopts the above-mentioned method 1 for manufacturing polarized glass to obtain polarized glass as shown in Table 3 and Table 4. In addition, the performance of each polarized glass is measured by the test method described in the present invention, and the measurement results are shown in Table 3 and Table 4. The thickness of the performance test sample in this embodiment is 0.5 mm.

[0109] Table 3.

[0110] Example 12# 13# 14# 15# 16# 17# <![CDATA[Si 4+ ]]> 32.64 37.99 36.5 40.81 36.8 35.83 <![CDATA[B 3+ ]]> 30.13 26.23 28.15 25.61 21.57 29.02 <![CDATA[Al 3+ ]]> 9.84 5.37 7.32 3.50 4.09 6.89 <![CDATA[Zr 4+ ]]> 1.85 1.48 1.51 1.45 0.68 0.89 <![CDATA[Li + ]]> 6.10 4.58 7.81 8.95 9.77 5.88 <![CDATA[K + ]]> 5.53 7.81 6.99 6.76 4.12 6.62 <![CDATA[Na + ]]> 10.02 13.96 7.30 11.72 20.49 13.45 <![CDATA[Zn 2+ ]]> 2.80 1.12 2.58 0.55 1.54 1.08 <![CDATA[Ti 4+ ]]> 0.86 1.43 1.75 0.56 0.78 0.27 <![CDATA[Ag + ]]> 0.15 0.02 0.03 0.04 0.10 0.03 <![CDATA[Cu 2+ ]]> 0.028 0 0.034 0.025 0.025 0.026 <![CDATA[Ce 4+ ]]> 0.052 0.01 0.026 0.025 0.035 0.014 Total cations 100 100 100 100 100 100 <![CDATA[O 2- ]]> 99.24 99.78 99.75 99.51 99.40 99.75 <![CDATA[Cl - ]]> 0.62 0.18 0.21 0.39 0.50 0.19 <![CDATA[Br - ]]> 0.14 0.04 0.04 0.10 0.10 0.06 Total anion 100 100 100 100 100 100 <![CDATA[B 3+ / At + ]]> 200.87 1311.50 938.33 640.25 215.70 967.33 <![CDATA[Ag + / This 4+ ]]> 2.88 2.00 1.15 1.60 2.86 2.14 Melting temperature(℃) 1280 1300 1330 1350 1250 1300 Clarifying temperature(℃) 1360 1380 1410 1430 1330 1380 Annealing temperature(℃) 550 550 550 580 500 550 Heat treatment temperature(℃) 700 650 700 700 600 680 Stretching temperature(℃) 620 620 630 630 600 620 Reduction temperature(℃) 430 220 350 360 380 350 Extinction ratio at 1550nm (dB) 34.9 28.2 28.6 30.5 31.5 30.3 Insertion loss at 1550nm(dB) 0.33 0.32 0.47 0.45 0.37 0.43 Extinction ratio at 1310nm (dB) 37.7 30.4 32.2 34.5 36.3 33.4 Insertion loss at 1310nm (dB) 0.63 0.60 0.62 0.50 0.48 0.42 Transmittance (%) 88.9 89.1 84.9 88.9 87.5 88.7

[0111] Table 4.

[0112] Comparative Example 18# 19# 20# 21# 22# <![CDATA[Si 4+ ]]> 39.55 37.86 32.21 38.88 44.88 <![CDATA[B 3+ ]]> 20.72 24.83 27.18 25.81 24.04 <![CDATA[Al 3+ ]]> 3.33 6.25 7.59 4.40 1.82 <![CDATA[Zr 4+ ]]> 0.34 1.11 1.22 0.36 1.70 <![CDATA[Li + ]]> 11.36 4.57 7.20 6.01 9.34 <![CDATA[K + ]]> 6.02 7.30 2.35 7.21 5.98 <![CDATA[Na + ]]> 16.45 14.96 18.47 13.68 9.56 <![CDATA[Zn 2+ ]]> 1.30 1.96 2.11 2.48 2.00 <![CDATA[Ti 4+ ]]> 0.8 1.14 1.62 1.14 0.58 <![CDATA[Ag + ]]> 0.08 0.01 0.02 0.02 0.04 <![CDATA[Cu 2+ ]]> 0.026 0 0.025 0 0.037 <![CDATA[Ce 4+ ]]> 0.024 0.01 0.005 0.01 0.023 Total cations 100 100 100 100 100 <![CDATA[O 2- ]]> 99.49 99.82 99.82 99.83 99.78 <![CDATA[Cl - ]]> 0.40 0.14 0.14 0.13 0.18 <![CDATA[Br - ]]> 0.11 0.04 0.04 0.04 0.04 Total anion 100 100 100 100 100 <![CDATA[B 3+ / At + ]]> 259.00 2483.00 1359.00 1290.50 601.00 <![CDATA[Ag + / This 4+ ]]> 3.20 2.00 4.00 1.43 1.74 Melting temperature(℃) 1300 1350 1230 1300 1400 Clarifying temperature(℃) 1380 1430 1310 1380 1480 Annealing temperature(℃) 550 580 500 550 600 Heat treatment temperature(℃) 610 580 500 550 600 Stretching temperature(℃) 600 630 590 630 640 Reduction temperature(℃) 380 250 320 300 400 Extinction ratio at 1550nm (dB) 31.7 20.0 29.6 28.3 31.7 Insertion loss at 1550nm(dB) 0.40 0.48 0.48 0.40 0.47 Extinction ratio at 1310nm (dB) 37.2 34.9 32.8 32.3 34.9 Insertion loss at 1310nm (dB) 0.60 0.61 0.61 0.52 0.60 Transmittance (%) 89.5 88.1 89.7 86.3 89.2

[0113] Figure 1This is the SEM image of Example 3. Figure 2 This is the SEM picture of the above-mentioned Example 14. The SEM refers to: the polarizing glass is surface treated by HF acid, the surface of the polarizing glass sample is sprayed with gold, and then analyzed by scanning electron microscope.

[0114] It can be seen from the above embodiments that, for the same glass components, the performance of the glass obtained by the second method for manufacturing polarized glass of the present invention is significantly better than that of the glass obtained by the first method for manufacturing polarized glass.

Claims

1. Polarized glass, characterized in that: Its components are expressed in molar percentage, and the cationic component contains: Si 4+ :28~55%、B 3+ :15~35%、R + :1~35%、Ag + :0.01~0.2%,the R + For Li + 、Na + , K + One or more of; The anion component contains: O 2- :99~99.9%、Cl - +Br - :0.1~1%.

2. The polarizing glass according to claim 1, characterized in that: Its components are expressed in molar percentages, and the cationic component also contains: Al 3+ :0~12%, and / or Zr 4+ :0~5%, and / or Zn 2+ :0~3.5%, and / or Ti 4+ :0~2%、and / or Cu 2+ :0~0.1%、and / or Ce 4+ :0~0.1%.

3. Polarized glass, characterized in that: Its components are expressed in molar percentage, and the cationic component consists of Si 4+ :28~55%、B 3+ :15~35%、R + :1~35%、Ag + :0.01~0.2%、Al 3+ :0~12%、Zr 4+ :0~5%、Zn 2+ :0~3.5%、Ti 4+ :0~2%、Cu 2+ :0~0.1%、Ce 4+ :0~0.1%composition, the R + For Li + 、Na + , K + One or more of; The anion component is O 2- :99~99.9% and Cl - +Br - : 0.1~1% composition.

4. The polarizing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: Ag + / Ce 4+ 0.5~4.5, preferably Ag + / Ce 4+ 1.0~3.0; and / or B 3+ / Ag + 150~2500, preferably B 3+ / Ag + It ranges from 200 to 1500.

5. The polarizing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, among which: Si 4+ :30~45%、and / or B 3+ :20~30%、and / or R + : 11-30%, preferably R + :20~30%, and / or Ag + :0.03~0.1%, and / or Al 3+ :3~10%, and / or Zr 4+ :0.5~3%, and / or Zn 2+ :0.5~2.5%, and / or Ti 4+ :0.5~1.5%, and / or Cu 2+ :0~0.05%, and / or Ce 4+ :0~0.06%.

6. The polarizing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: Li + : 0-12%, preferably Li + :0~9%、and / or Na + : 0-25%, preferably Na + :5~15%、and / or K + : 0~10%, preferably K + :2~8%.

7. The polarizing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: 2- :99.4~99.9%, and / or Cl - +Br - :0.1~0.6%.

8. The polarizing glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in molar percentage, where: Cl - :0.1~0.8%, preferably Cl - :0.1~0.5%, and / or Br - : 0~0.3%, preferably Br - :0~0.2%.

9. The polarizing glass according to any one of claims 1 to 3, characterized in that: Polarized glass with a thickness of less than 0.8 mm has a transmittance of more than 80%, preferably more than 85%, and more preferably more than 90%; and / or the extinction ratio at 1550 nm is more than 20 dB, preferably more than 30 dB, and more preferably more than 40 dB; and / or the extinction ratio at 1310 nm is more than 30 dB, preferably more than 40 dB, and more preferably more than 50 dB; and / or the insertion loss at 1550 nm is less than 0.50 dB, preferably less than 0.40 dB, and more preferably less than 0.30 dB; and / or the insertion loss at 1310 nm is less than 0.70 dB, preferably less than 0.60 dB, and more preferably less than 0.40 dB.

10. Matrix glass, characterized in that Its components are expressed in molar percentage, and the cationic component contains: Si 4+ :28~55%、B 3+ :15~35%、R + :1~35%、Ag + :0.01~0.2%,the R + For Li + 、Na + , K + One or more of; The anion component contains: O 2- :99~99.9%、Cl - +Br - :0.1~1%.

11. The matrix glass according to claim 10, characterized in that Its components are expressed in molar percentages, and the cationic component also contains: Al 3+ :0~12%, and / or Zr 4+ :0~5%, and / or Zn 2+ :0~3.5%, and / or Ti 4+ :0~2%, and / or Cu 2+ :0~0.1%、and / or Ce 4+ :0~0.1%.

12. The matrix glass according to claim 10 or 11, characterized in that: Its components are expressed in molar percentage, where: Ag + / Ce 4+ 0.5~4.5, preferably Ag + / Ce 4+ 1.0~3.0; and / or B 3+ / Ag + 150~2500, preferably B 3+ / Ag + It ranges from 200 to 1500.

13. The matrix glass according to claim 10 or 11, characterized in that: Its components are expressed in molar percentage, among which: Si 4+ :30~45%、and / or B 3+ :20~30%、and / or R + : 11-30%, preferably R + :20~30%, and / or Ag + :0.03~0.1%, and / or Al 3+ :3~10%, and / or Zr 4+ :0.5~3%, and / or Zn 2+ :0.5~2.5%, and / or Ti 4+ :0.5~1.5%, and / or Cu 2+ :0~0.05%, and / or Ce 4+ :0~0.06%.

14. The matrix glass according to claim 10 or 11, characterized in that: Its components are expressed in molar percentage, where: Li + : 0-12%, preferably Li + :0~9%、and / or Na + : 0-25%, preferably Na + :5~15%、and / or K + : 0~10%, preferably K + :2~8%.

15. The matrix glass according to claim 10 or 11, characterized in that: Its components are expressed in molar percentage, where: 2- :99.4~99.9%, and / or Cl - +Br - :0.1~0.6%.

16. The matrix glass according to claim 10 or 11, characterized in that: Its components are expressed in molar percentage, where: Cl - :0.1~0.8%, preferably Cl - :0.1~0.5%, and / or Br - : 0~0.3%, preferably Br - :0~0.2%.

17. A polarizing element, characterized in that Made of the polarizing glass described in any one of claims 1 to 9.

18. A device, characterized in that A polarizing glass comprising any one of claims 1 to 9, or a polarizing element comprising claim 17.

19. A method for manufacturing polarized glass, characterized in that: The method comprises the following steps: 1) forming a matrix glass; 2) heat treatment; 3) stretching treatment; 4) reduction treatment.

20. The method for manufacturing polarizing glass according to claim 19, characterized in that: The ultraviolet exposure treatment is performed before the heat treatment in step 2).

21. The method for manufacturing polarizing glass according to claim 20, characterized in that: The ultraviolet exposure treatment is: cutting the matrix glass into long strips and performing large-surface polishing, and then performing ultraviolet exposure on the matrix glass. Preferably, the ultraviolet exposure wavelength is 308-320nm, and the ultraviolet exposure time is preferably greater than 0 but less than or equal to 30 minutes, more preferably 10-25 minutes, and further preferably 15-25 minutes.

22. The method for manufacturing polarizing glass according to any one of claims 19 to 21, characterized in that: The melting temperature of the matrix glass is 1200-1400°C, the melting time is 5-20 hours, the clarification temperature is 1300-1500°C, the clarification time is 6-8 hours, the annealing temperature is 500-600°C, the annealing time is 6-10 hours, and an oxidizing gas is introduced into the smelting furnace during the smelting process.

23. The method for manufacturing polarizing glass according to any one of claims 19 to 21, characterized in that: The heat treatment is: heating the matrix glass at a temperature ≥ T g + (100-200°C) for 10-20 hours. g is the transition temperature of the matrix glass.

24. The method for manufacturing polarizing glass according to any one of claims 19 to 21, characterized in that: The stretching process is: at T f ~(T f The glass is stretched at a temperature of 50°C to stretch the spherical silver halide clusters inside the glass into long strips or elliptical clusters with an aspect ratio of ≥2:

1. f is the softening temperature of the matrix glass.

25. The method for manufacturing polarizing glass according to any one of claims 19 to 21, characterized in that: The reduction treatment is: reducing the glass in a reducing atmosphere so that the long strips or elliptical silver halide clusters on the surface of the glass are reduced to elemental silver. The reduction temperature is preferably greater than 200° C. but less than the melting point of the silver halide.